(7n-6)+2=1

Simple and best practice solution for (7n-6)+2=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7n-6)+2=1 equation:


Simplifying
(7n + -6) + 2 = 1

Reorder the terms:
(-6 + 7n) + 2 = 1

Remove parenthesis around (-6 + 7n)
-6 + 7n + 2 = 1

Reorder the terms:
-6 + 2 + 7n = 1

Combine like terms: -6 + 2 = -4
-4 + 7n = 1

Solving
-4 + 7n = 1

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 7n = 1 + 4

Combine like terms: -4 + 4 = 0
0 + 7n = 1 + 4
7n = 1 + 4

Combine like terms: 1 + 4 = 5
7n = 5

Divide each side by '7'.
n = 0.7142857143

Simplifying
n = 0.7142857143

See similar equations:

| 375+12h=280+15h | | -10n+2(.9-9n)=5.8 | | 8x(x-5)=4x-10+3x-30 | | 12x+y=-60 | | -5(7-x+5x)= | | -5n+6=-35n-42-6n | | 16=[2w+w-1] | | 7y+27=6y-3 | | 3(60)-3x=99 | | 50+3x=14 | | 9a-9.4=8a+4.6 | | -6+x=19 | | -2-2x-5x=-37 | | 8(3-2)=104 | | (y^2-7y-5)-(-3y^2+3y-4)= | | 2(5r+45)=20(2r-24) | | 5n+7+n=3n-2+4n(2n+1) | | t=4+3x | | -10-(-5x)=5x | | 3x+11-x=8+4x-5 | | -4.4+6.2=5x-2.9-4x | | x=4+3t | | 2+0.5x=3-5x | | 7-3u^2=1 | | 50+3x=4 | | x+65+57=90 | | 7(9n-4)= | | 5=12(2cosx+sinx) | | 4x+9x-3x=37+3 | | Y=6x^2-13x-8 | | 2c+4d=4 | | 7x+2(x-14)=80 |

Equations solver categories